A Novel Cellular Pathway of Antigen Presentation and CD4 T Cell Activation in vivo - Scales, Hannah E.; Meehan, Gavin R.; Hayes, Alan J.; Benson, Robert A.; Watson, Emma; Walters, Anne; Tomura, Michio; Maraskovsky, Eugene; Garside, Paul; Baz Morelli, Adriana; Brewer, James M. (Frontiers in Immunology, 2018)
Dendritic cell activation of CD4 T cells in the lymph node draining a site of infection or vaccination is widely considered the central event in initiating adaptive immunity. The accepted dogma is that this occurs by stimulating local activation and antigen acquisition of dendritic cells, with subsequent lymph node migration, however the generalizability of this mechanism is unclear. Here we show that in some circumstances antigen can bypass the injection site inflammatory response, draining freely and rapidly to the lymph nodes where it interacts with subcapsular sinus (SCS) macrophages resulting in their death. Debris from these dying SCS macrophages is internalized by monocytes recruited from the circulation. This coordinated response leads to antigen presentation by monocytes and interactions with naïve CD4 T cells may be driving the initiation of T cell and B cell responses. These studies demonstrate an entirely novel pathway leading to initiation of adaptive immune responses in vivo.